SAT0613-HPR EFFECT OF CERVICAL STABILIZATION EXERCISES ON CERVICAL POSITION ERROR IN PATIENTS WITH SPONDYLOARTHRITIS: A RANDOMIZED CONTROLLED TRIAL. (2nd June 2020) - Oz, H. E.; Bayraktar, D.; Kara, M.; Solmaz, D.; Akar, S.
Abstract : Background: Proprioception sense might be deteriorated due to joint related diseases. Different exercise programs were shown beneficial for improving proprioception sense. However, the effect of exercise on cervical position error was not investigated in patients with axial spondyloarthritis (axSpA). Objectives: To investigate the effect of cervical stabilization exercises on cervical position error in patients with axSpA. Methods: Thirty-nine patients with axSpA were randomly allocated into two groups as exercise group (n: 20, 11 males) and control group (n: 19, 12 males). All patients were evaluated regarding to physical characteristics (age, body-mass index), disease activity (Bath Ankylosing Spondylitis Disease Activity Index), functional status (Bath Ankylosing Spondylitis Functional Index), and spinal mobility (Bath Ankylosing Spondylitis Metrology Index). Cervical position error was evaluated in flexion, extension, rotation and lateral flexion directions and was calculated using a special formula (1). All evaluations were performed at baseline and after six weeks. Exercise group performed a progressive home-based cervical stabilization exercise program, while the control group did not receive any exercise intervention. Exercise adherence control and exercise progression was delivered by sending messages and video instructions via a freeware and cross-platform messaging service (WhatsApp Messenger) in a weekly basis. Results: Baseline physical and disease related characteristics were similar between groups (p>0.05, table 1 ). Exercise group showed significant improvements in all directions related to cervical proprioception following six weeks (p<0.05, Table 2 ), however, no improvements were observed in the control group (p>0.05, Table 2 ). Conclusion: A six-week cervical stabilization exercise program is beneficial for impaired cervical proprioception sense in patients with axSpA. References: [1]Dugailly P-M, De Santis R, Tits M, Sobczak S, Vigne A, Feipel V. Head repositioning accuracy in patients with neck pain and asymptomatic subjects: concurrent validity, influence of motion speed, motion direction and target distance. European Spine Journal. 2015;24:2885-2891. Disclosure of Interests: None declared